Rates and controls of nitrification in a large oligotrophic lake. (14th December 2012) - Small, Gaston E.; Bullerjahn, George S.; Sterner, Robert W.; Beall, Benjamin F. N.; Brovold, Sandra; Finlay, Jacques C.; McKay, Robert M. L.; Mukherjee, Maitreyee
Abstract : Recent discoveries have altered prevailing paradigms concerning the conditions under which nitrification takes place and the organisms responsible for nitrification in aquatic ecosystems. In Lake Superior, nitrate () concentrations have increased fivefold in the past century. Although previous evidence indicated that most is generated by nitrification within the lake, important questions remain concerning the magnitude and controls of nitrification, and which microbial groups are primarily responsible for this process. We measured water‐column nitrification rates in the western basin of Lake Superior during five research cruises from November 2009 to March 2011. Using in situ bottle incubations at 10 depths, we quantified nitrification rates using both the oxidation of 15 N‐labeled ammonium () and the uptake of 14 C associated with nitrification. Average rates of oxidation ranged from 18–34 nmol N L −1 d −1 across the five cruises, similar to values reported for the coastal ocean, and two orders of magnitude lower than values reported from other lakes. Low nitrification rates observed in the epilimnion corresponded to the absence of ammonium‐oxidizing archaea and nitrite‐oxidizing bacteria. The measured rates of nitrification are > 50‐fold greater than the long‐term rise in the lake, indicating that N is actively cycling and that long‐term change in this ecosystem is mediated by internal dynamics.